Intergenerational support and depressive symptoms in old age: The difference between urban and rural China - Wang, Chenxi; Liu, Zhengkui; Chen, Tianyong; Wang, Jinfeng; Zhang, Xin; Han, Buxin (Frontiers in Public Health, 2022)
Objectives Intergenerational support is associated with fewer depressive symptoms in old age. Uneven development has resulted in huge urban–rural disparities in China, which could lead to different intergenerational relationships. The present study aimed to examine whether intergenerational support was associated with depressive symptoms differently among urban and rural Chinese older participants. Methods A sample of 3,498 participants from nine pairs of urban subdistricts and rural villages were included in the present study. Depressive symptoms were measured by the 10-item Center for Epidemiological Studies Depression Scale, and the intergenerational support mechanisms (financial, instrumental, and emotional) were assessed with a self-designed questionnaire. Results Significant areas by support effect for depressive symptoms indicated different associations between intergenerational financial and emotional support and depressive symptoms in urban and rural areas. Specifically, urban older participants receiving emotional support from adult children and rural older participants receiving financial support from adult children showed fewer depressive symptoms. In both areas, participants receiving instrumental support showed fewer depressive symptoms. Conclusion Our study is the first to compare the urban–rural disparity in association between intergenerational support and depressive symptoms in a developing country, China. The results support modernization theories proposing weakened economic function but intensified emotional ties in societies with higher level of development. Communication-based intergenerational emotional support should be promoted in urban areas, and formal support systems should provide financial and instrumental support to the vulnerable rural older population.